United Kingdom : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report, 2010)
The U.K. economy is on the mend, but crisis-related scars still need healing. The challenge ahead will be to ensure sustainable recovery and balance sheet repair while remaining flexible to respond to shocks. A highly accommodative monetary stance is required to offset the contractionary impulse from fiscal policy and keep inflation close to target. Risks to this scenario are substantial, and policies will need to adapt if they materialize. The government should continue to fortify fiscal institutions. Efforts should continue to strengthen financial sector health.